The effect of the financial crisis on older households in England - James Banks; Rowena Crawford; Thomas Crossley; Carl Emmerson (Institute for Fiscal Studies (IFS), 2012)
Prices of real and financial assets fell substantially in the UK during 2008-09. The fourth wave of the English Longitudinal Study of Ageing (ELSA) was in the field throughout this 'financial crisis'. We use these data and earlier ELSA waves first to document the effect of the crisis on the finances of those aged 50 and over in England, and second, to estimate the effect of wealth shocks on household consumption and individual expectations of the future. Many household experienced a significant wealth shocks, but these shocks led to modest spending effects and small revisions to expectations regarding future bequests. Expectations of bequests seem particularly tied to housing wealth.
Keywords: D12; D14; E21; G01; G11; 330; consumption; expectations; financial crisis; wealth